Identification of Uterine Microbiota in Infertile Women Receiving in vitro Fertilization With and Without Chronic Endometritis - Chen, Weijun; Wei, Kehong; He, Xia; Wei, Jing; Yang, Lijuan; Li, Lin; Chen, Tingtao; Tan, Buzhen (Frontiers in Cell and Developmental Biology, 2021)
In vitro fertilization (IVF) is an important assisted reproductive technology in treating infertility, whose failure rate is still high. Studies suggested that uterine microbiota are related to women's reproductive diseases and persisting intrauterine bacterial infectious conditions, such as chronic endometritis (CE), impair the pregnancy processes. But the relationship between uterine microbiota and IVF outcomes is still an open question. In the present study, ninety-four patients diagnosed with infertility were enrolled and were divided into CE and non-CE groups depending on the hysteroscopy and immunohistochemistry. Subsequently, these two groups were divided into pregnancy and non-pregnancy groups depending on the IVF outcomes, respectively. The uterine fluids were collected and underwent high-throughput sequencing for microbial analysis. The results demonstrated that CE seriously affected the IVF outcomes, and patients with CE had significant lower clinical pregnancy rate compared with the non-CE patients (32% vs. 58.42%, P=0.0014). The relative abundances of Proteobacteria, and Acidobacteria were higher in the non-CE group, whereas high abundances of Actinobacteria and Fusobacteria were observed in the CE group at phylum level. At the genus level, high relative abundances of Gardnerella were observed in the CE group and non-pregnancy groups, which significantly referred to the negative IVF outcome. In conclusion, CE maybe a key factor for the negative outcome of IVF, of which the uterine microbiota play a pivotal role, and the microbial diversity in uterine may be served as a biomarkers to forecast the success of IVF outcome.